Click Chemistry and ATRP: A Beneficial Union for the Preparation of Functional Materials - Golas, Patricia L.; Matyjaszewski, Krzysztof (QSAR & combinatorial science, 2007)
Since the concept of highly efficient and selective “click” reactions was put forth by Sharpless and coworkers, this branch of chemical transformations has been subject to an astounding degree of applications. Although click chemistry encompasses a wide variety of reactions, the CuI‐catalyzed azide–alkyne cycloaddition has received the most attention. It has been increasingly employed in polymer functionalization and materials synthesis, especially in conjunction with controlled radical polymerization methods, such as Atom Transfer Radical Polymerization (ATRP). The CuI‐catalyzed azide–alkyne cycloaddition is utilized particularly well with ATRP, due to the ease of incorporating clickable functionality into polymers prepared by ATRP and the use of the same catalyst in each process. This minireview summarizes and analyzes recent developments in the field of CuI‐click chemistry as applied to ATRP, and how the combination of these two powerful techniques has greatly expanded the range of available materials and has contributed to fundamental understanding of this process.